Benefit and harm of intravenous vasodilators across the clinical profile spectrum in acute cardiogenic pulmonary oedema patients. Issue 5 (August 2020) - Shiraishi, Yasuyuki; Kohsaka, Shun; Katsuki, Toshiomi; Harada, Kazumasa; Miyazaki, Tetsuro; Miyamoto, Takamichi; Matsushita, Kenichi; Iida, Kiyoshi; Takei, Makoto; Yamamoto, Yoshiya; Shindo, Akito; Kitano, Daisuke; et al.
Background: The absence of high quality, large-scale data that indicates definitive mortality benefits does not allow for firm conclusions on the role of intravenous vasodilators in acute heart failure. We aimed to investigate the associations between intravenous vasodilators and clinical outcomes in acute heart failure patients, with a specific focus on patient profiles and type of vasodilators. Methods: Data of 26, 212 consecutive patients urgently hospitalised for a primary diagnosis of acute heart failure between 2009 and 2015 were extracted from a government-funded multicentre data registration system. Propensity scores were calculated with multiple imputations and 1:1 matching performed between patients with and without vasodilator use. The primary endpoint was inhospital mortality. Results: On direct comparison of the vasodilator and non-vasodilator groups after propensity score matching, there were no significant differences in the inhospital mortality rates (7.5% vs. 8.8%, respectively; P =0.098) or length of intensive/cardiovascular care unit stay and hospital stay between the two groups. However, there was a substantial difference in baseline systolic blood pressure by vasodilator type; favourable impacts of vasodilator use on inhospital mortality were observed among patients who had higher systolic blood pressures and those who had no atrial fibrillation on admission. Furthermore, when compared to nitrates, the use of carperitide (natriuretic peptide agent) was significantly associated with worse outcomes, especially in patients with intermediate systolic blood pressures. Conclusions: In acute heart failure patients, vasodilator use was not universally associated with improved inhospital outcomes; rather, its effect depended on individual clinical presentation: patients with higher systolic blood pressure and no atrial fibrillation seemed to benefit maximally from vasodilators. Trial registration: UMIN-CTR identifier, UMIN000013128